AML-Related NPM Mutations Drive p53 Delocalization into the Cytoplasm with Possible Impact on p53-Dependent Stress Response - Holoubek, Aleš; Strachotová, Dita; Otevřelová, Petra; Röselová, Pavla; Heřman, Petr; Brodská, Barbora (Cancers, 2021)
Nucleophosmin (NPM) interaction with tumor suppressor p53 is a part of a complex interaction network and considerably affects cellular stress response. The impact of NPM1 mutations on its interaction with p53 has not been investigated yet, although consequences of NPMmut-induced p53 export to the cytoplasm are important for understanding the oncogenic potential of these mutations. We investigated p53-NPM interaction in live HEK-293T cells by FLIM-FRET and in cell lysates by immunoprecipitation. eGFP lifetime-photoconversion was used to follow redistribution dynamics of NPMmut and p53 in Selinexor-treated cells. We confirmed the p53-NPMwt interaction in intact cells and newly documented that this interaction is not compromised by the NPM mutation causing displacement of p53 to the cytoplasm. Moreover, the interaction was not abolished for non-oligomerizing NPM variants with truncated oligomerization domain, suggesting that oligomerization is not essential for interaction of NPM forms with p53. Inhibition of the nuclear exporter XPO1 by Selinexor caused expected nuclear relocalization of both NPMmut and p53. However, significantly different return rates of these proteins indicate nontrivial mechanism of p53 and NPMmut cellular trafficking. The altered p53 regulation in cells expressing NPMmut offers improved understanding to help investigational strategies targeting these mutations.
Keywords: p53; FLIM-FRET; photoconversion; acute myeloid leukemia; nucleophosmin; mutation; Selinexor